2021
DOI: 10.3390/microorganisms10010001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metarhizium anisopliae–Chitosan Nanoparticles and Their Pathogenicity against Plutella xylostella (Linnaeus)

Abstract: Nanotechnology is increasingly being used in areas of pesticide production and pest management. This study reports the isolation and virulence of a new Metarhizium anisopliae isolate SM036, along with the synthesis and characterization of M. anisopliae–chitosan nanoparticles followed by studies on the efficacy of nanoparticles against Plutella xylostella. The newly identified strain proved pathogenic to P. xylostella under laboratory conditions. The characterization of M. anisopliae–chitosan nanoparticles thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Combinations of chitosan and biocontrol (entomopathogenic and nematophagous) fungi are currently developed for enhancing fungal pathogenicity and plant defence abilities. This has been reported for Beauveria bassiana ( Abdullah and Sukar, 2021 ) and Metarhizium anisopliae ( Wu et al., 2021 ). Nematophagous fungi have also demonstrated to be more efficient for biological control when combined with chitosan than on their own ( Escudero et al., 2017 ; Singh and Chittenden, 2021 ; Kappel et al., 2022 ).…”
Section: Chitosan and Biological Control Fungisupporting
confidence: 69%
“…Combinations of chitosan and biocontrol (entomopathogenic and nematophagous) fungi are currently developed for enhancing fungal pathogenicity and plant defence abilities. This has been reported for Beauveria bassiana ( Abdullah and Sukar, 2021 ) and Metarhizium anisopliae ( Wu et al., 2021 ). Nematophagous fungi have also demonstrated to be more efficient for biological control when combined with chitosan than on their own ( Escudero et al., 2017 ; Singh and Chittenden, 2021 ; Kappel et al., 2022 ).…”
Section: Chitosan and Biological Control Fungisupporting
confidence: 69%
“…The study involved feeding cabbage leaves that had been dipped in AgNPs to the insects, demonstrating the nanoparticles’ pesticidal properties. Wu et al [ 59 ] reported the insecticidal effects of mycosynthesized CsNPs against P. xylostella by applying them through a spray onto cabbage leaves. Alfy et al [ 60 ] conducted a study investigating the insecticidal properties of CsNPs on Meloidogyne incognita , Locusta migratoria , and Spodoptera littoralis .…”
Section: Resultsmentioning
confidence: 99%
“…The incubated sample was centrifuged at a speed of 2744 RCF for 20 minutes at 28℃. The supernatant was removed, while the pellet was cleansed with distilled water, and kept at -20℃ for 2 days (Wu et al, 2021). The control used in this research was a 40% nanocellulose formulation.…”
Section: Formulationmentioning
confidence: 99%